Repurposing antifungals: population pharmacokinetics of itraconazole and hydroxy-itraconazole following administration of a nanocrystal formulation - Jansen, Anouk M E; Ter Heine, Rob; Donnelly, J P; Blijlevens, Nicole; Brüggemann, Roger J M (Journal of antimicrobial chemotherapy, 2023)
Abstract Objectives To describe itraconazole and hydroxy-itraconazole pharmacokinetics following intravenous (IV) administration of a previously developed nanocrystal formulation (NCF) in haematopoietic cell transplant (HCT) recipients for prophylaxis of invasive fungal disease. Methods In a prospective Phase II study, 10 HCT recipients received itraconazole NCF administered in 2-hour infusions of 200 mg twice daily for 2 days, followed by 200 mg once daily until Day 14. Full pharmacokinetic curves were obtained on Days 7 and 14. Additional samples were collected pre- and post-infusion until Day 6, pre-infusion on Days 10 and 12, and during washout on Days 16, 17, 18, 19 and 28. Itraconazole and hydroxy-itraconazole pharmacokinetics were analysed by non-linear mixed-effects population pharmacokinetic modelling. Results Four-hundred and seventy-one itraconazole and 471 paired hydroxy-itraconazole concentrations from 10 patients were included for analysis. Data were best described by a semi-mechanistic model with central and peripheral itraconazole compartments and a hydroxy-itraconazole compartment with dissolution of itraconazole drug particles from nanocrystals and first-order distribution and elimination. The final model included interindividual variability on itraconazole clearance and hydroxy-itraconazole clearance. Conclusions This study provides information on the pharmacokinetic properties of the itraconazole NCF useful for development of this formulation. Our results suggest that itraconazole NCF is a suitable formulation and may warrant renewal in the setting of repurposing. Our findings may be useful for the reformulation of other highly lipophilic compounds as well.